PENGARUH PELATIHAN DAN PENGGUNAAN TEKNOLOGI TERHADAP PRODUKTIVITAS DAN KEBERLANJUTAN UMKM DI KOTA DENPASAR - Andiana, I Kadek Agus Krisna; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
The COVID-19 pandemic has brought great challenges to the development of the economic sector, especially in maintaining the sustainability of MSME businesses. The purpose of this study was to analyze and determine the effect of training and use of technology on the productivity of MSMEs in Denpasar City; the effect of training, use of technology and productivity on the sustainability of MSMEs in Denpasar City, productivity in mediating the effect of training and use of technology on the sustainability of MSMEs in Denpasar City. The data source is primary data by conducting a questionnaire as many as 100 MSME actors with a proportionale stratified random sampling method. The data analysis technique is path analysis technique. The results of this study indicate that the variables of training and the use of technology have a positive and significant effect on the productivity of MSMEs in Denpasar City. The variables of training, use of technology and productivity have a positive and significant impact on the sustainability of MSMEs in Denpasar City. Productivity mediates the effect of training and use of technology on the sustainability of MSMEs in Denpasar City.   Keywords: Training, Use of Technology, Productivity, MSME Sustainability.